2009
DOI: 10.1051/0004-6361/200810698
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic binaries among Hipparcos M giants

Abstract: Context. This paper is a follow-up on the vast effort to collect radial velocity data for stars belonging to the Hipparcos survey. Aims. We aim at extending the orbital data available for binaries with M giant primaries. The data presented in this paper will be used in the companion papers of this series to (i) derive the binary frequency among M giants and compare it to that of K giants (Paper II); and (ii) analyse the eccentricity -period diagram and the mass-function distribution (Paper III). Methods. Keple… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 49 publications
1
37
0
Order By: Relevance
“…The object HD 190658 (V1472 Aql, HR 7680, HIP 98954) is a M2.5 III star in a binary system with a relatively short orbital period (P = 198.716 days; Lucke & Mayor 1982) -the second smallest in the sample of Famaey et al (2009). It is in a sense a sister system to the symbiotic star SS Lep, with a similar period, and therefore deserves further study.…”
Section: Hd 190658mentioning
confidence: 98%
“…The object HD 190658 (V1472 Aql, HR 7680, HIP 98954) is a M2.5 III star in a binary system with a relatively short orbital period (P = 198.716 days; Lucke & Mayor 1982) -the second smallest in the sample of Famaey et al (2009). It is in a sense a sister system to the symbiotic star SS Lep, with a similar period, and therefore deserves further study.…”
Section: Hd 190658mentioning
confidence: 98%
“…Independent of our study, Ortiz & Guerrero (2016) studied a volume-limited (< 500 pc) sample of 53 AGB stars detected by GALEX. This study includes the samples of Sahai et al (2008) and "confirmed" binary AGB stars derived from a radial velocity (RV) study by Famaey et al (2009) 5 . Ortiz & Guerrero (2016) esti-5 Sahai et al (2008 and Famaey et al (2009) remark on the complications that pulsations of AGB stars pose for RV measurements of such stars.…”
Section: Scattering Of the Interstellar Radiation Fieldmentioning
confidence: 99%
“…This study includes the samples of Sahai et al (2008) and "confirmed" binary AGB stars derived from a radial velocity (RV) study by Famaey et al (2009) 5 . Ortiz & Guerrero (2016) esti-5 Sahai et al (2008 and Famaey et al (2009) remark on the complications that pulsations of AGB stars pose for RV measurements of such stars. Nevertheless, Famaey et al (2009) conclude that some of the Mira and semi-regular variables they studied are mated the NUV and FUV flux in excess of photospheric emission based on stellar spectral templates and proposed that if an AGB star had a NUV excess ≥ 20 and/or if an AGB star is detected in FUV, then its UV emission indicates a binary companion.…”
Section: Scattering Of the Interstellar Radiation Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a binary companion is an implausible explanation for the observed polarization. We also note that Famaey et al (2009) found no evidence that V CVn is a spectroscopic binary.…”
Section: Binary Companionmentioning
confidence: 58%